Lymphatic Filariasis Epidemiology, Treatment and Prevention - The Indian Perspective (Springer Singapore, 2018)
Lymphatic Filariasis (LF) is a group of human and animal infectious diseases caused by nematode parasites of the order Filariidae. Often neglected, it is one of the oldest and the most debilitating tropical diseases (NTDs), transmitted from human to human by mosquitoes bites, particularly the brown black mosquito known as Culex quinquifasciatus. LF is a major public health problem in many parts of the tropics, especially India, which accounts for as much as 40% of total global cases. As a leading cause of permanent and long-term disability worldwide, the parasite infection imposes a severe physical and socioeconomic burden. The World Health Organization (WHO) estimates that 1.4 billion people live in high-risk areas - 120 million of which are already infected with LF, including 22 million children below the age of 15 and about 76 million who suffer from damaged lymphatic and renal systems. India has made great strides toward eliminating the disease, and these advances are of global significance. They include early diagnosis mechanisms, vaccine product development, detection of parasites in the vector, and studies on parasite evolution trends in nature as warning signals. Reports on the successes and failures are needed to enable measures to be taken to avoid disaster and ensure a smooth transition from endemicity in India to the elimination of lymphatic filariasis by 2020. This book, which gathers highly original contributions on various subjects related to lymphatic filariasis, discusses the latest scientific research that will help the nation to achieve this milestone. It also serves as a guide to many other countries struggling against this highly debilitating and incapacitating disease.